DI-081 Uninsured patients: tools aimed at safe dispensing. (24th February 2014) - Richard, C; Sigward, E; Fratta, A; Benoit, G
Abstract : Background: In France, uninsured patients, mainly foreigners, are allowed free access to healthcare. The pharmacy staff of our paediatric hospital dispenses treatments for their children. A problem of understanding may arise with parents who do not speak French fluently. This may lead to poor compliance leading to ineffectiveness or toxicity. In paediatrics, the risk of mistakes is important because there are few pharmaceutical forms for kids. Purpose: To create tools to help the pharmacy technicians dispense safely. Materials and methods: A retrospective analysis of prescriptions for uninsured patients over one year was performed to have demographic and medical descriptions of this population. We also discussed the following matters with the technicians: tools used or desired, medicines most often involved, patient understanding. Those two synthetic approaches have permitted the development of necessary tools and their creation. Results: During the study period, 370 prescriptions were dispensed to 235 patients. 63% of the prescriptions were for children, 17% for adults and 20% did not mention the age. Three categories of prescriptions were found: chronic pathologies (epilepsy, sickle cell anaemia and asthma), acute pathologies (pain/fever, infections) and discharge from maternity department. The prescribing departments were: Emergencies (44%), Maternity - Gynaecology (20%), Paediatrics (11%), other (25%). The most prescribed drugs were: paracetamol syrup (16%), vitamin D and vitamin K1 (8%), physiological saline solution for nose wash (6%) and antibiotics (4%). The investigation conducted among the technicians (n = 9) showed that they used mime (8/9), drawings (6/9) or called colleagues (4/9). 8 out of 9 technicians assessed that patient understanding was weak and among other things they wanted synthetic instruction cards (6/9), administration plans (4/9) and a lexicon (4/9). Therefore we devised a variety of tools: 13 synthetic instruction cards in French and English (paracetamol syrup, dilution…), a French-English lexicon and three administration plans (3 doses in 24 h, 6 doses in 24 h and a weekly administration plan). Conclusions: Uninsured patients must not be neglected: treatment misunderstanding may lead to serious consequences, so the various tools were devised. Several goals ensue from this study. In the short term, we need to evaluate the provision and the benefit of those different tools. In the medium term, the validated tools created in this study will be spread to other pharmacy hospitals. No conflict of interest.